Characterization of bacterial cellulose nanocrystals: Effect of acid treatments and neutralization. (30th January 2021) - Arserim-Uçar, Dılhun Keriman; Korel, Figen; Liu, LinShu; Yam, Kit L.
Highlights: Bacterial cellulose nanocrystals were successfully prepared from Gluconacetobacter xylinus . Negatively charged nanocellulose crystals were obtained. Nanocellulose crystals were obtained with high thermal stability and crystallinity. High crystalline nanocrystals could be used for cellulose-based formulations for food applications. Abstract: In this study, bacterial cellulose nanocrystals (BCNCs) were obtained from bacterial cellulose nanofibers (BCNFs) by controlled hydrolysis of sulfuric and hydrochloric acids. The influence of hydrolysis temperature and acid type with the addition of the post-treatment step was studied. The obtained BCNCs were analyzed based on the structural characterization and the properties of the nanocrystals. The BCNCs crystallinity increased, and the size of nanocrystals decreased with increasing 10 °C hydrolysis temperature for both acid hydrolysis conditions. Hydrolysis conditions with neutralization post-treatment did not alter the thermal stability of nanocrystals, and BCNCs had high thermal stability like raw BCNFs. Elemental analysis results indicated that sulfur content (S %) was very low for sulfuric acid hydrolyzed samples, and X-ray results did not show any sulfate salt peaks. Thermal stable BCNCs with high crystallinity were successfully produced to meet the process requirements in various applications, especially in the food industry.